Design of phononic crystals plate and application in vehicle sound insulation. (November 2018) - Li, Lijun; Gang, Xianyue; Sun, Zhenyong; Zhang, Xianxu; Zhang, Fan
Highlights: A new type of phononic crystals with micro perforated plate structure is proposed. The new structure is applied to automobile and can reduce noise in the cab. The sound insulation performance of some phononic crystals plates are analyzed. Abstract: The sound insulation performance of plates obviously affects the noise inside vehicle. Phononic crystals are periodic structures composed of various elastic materials. In this paper, the sound insulation performance of commonly used phononic crystals plates are analyzed by FEM (Finite Element Method), and some relevant conclusions are obtained. Based on the common two-dimensional convex phononic crystals, combined with micro perforated plate, a new type of phononic crystals plate is proposed, and the new combined phononic crystals structure is applied to the front plate of some automobile. The analysis results show that the combined phononic crystals plate has obvious effect on the noise reduction of the cab.